Carbon-Tolerant Ni/ScCeSZ via Aqueous Tape Casting for IT- SOFCs. (30th May 2017) - Arifin, Nor; Button, Tim; Steinberger-Wilckens, Robert
Abstract : Nickel-yttria stabilized zirconia (Ni/8YSZ) and nickel-ceria doped-scandia stabilised zirconia (Ni/10ScCeSZ) anode supported cells were successfully fabricated using a reverse aqueous tape casting method. The performances of the full cells were tested using both hydrogen and dry biogas at the anode side and ambient air at the cathode side in the temperature range 750°C to 800°C. In hydrogen, Ni/10ScCeSZ showed better performance at 800°C compared to the Ni/8YSZ cell. Switching the fuel from hydrogen to dry biogas, the performance of the Ni/8YSZ cell reduced significantly from 0.31 W/cm 2 to 0.06 W/cm 2 . With Ni/10ScCeSZ cells, the cell performance in biogas was 4 times higher than the corresponding Ni8YSZ cells. The maximum power density decreased only from 0.36 W/cm 2 to 0.22 W/cm 2 in Ni/10ScCeSZ cell tested when switched from hydrogen to biogas. The results of this work indicate the possibility of using biogas or other carbonaceous fuels in SOFCs without the addition of water (steam).